2009
DOI: 10.1530/eje-09-0572
|View full text |Cite
|
Sign up to set email alerts
|

Comparing progression of non-functioning pituitary adenomas in hypopituitarism patients with and without long-term GH replacement therapy

Abstract: Objective: An important safety issue with GH replacement therapy (GHRT) in hypopituitary patients with a history of a pituitary adenoma is the risk for tumour recurrence or enlargement. Design: Case-control study. Subjects and methods: We studied tumour progression rate in 121 patients with hypopituitarism on the basis of non-functioning pituitary adenomas (NFPA) receiving long-term GHRT. A group of 114 NFPA patients not receiving GHRT who were matched in terms of duration of follow-up, gender, age, age at dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 46 publications
5
25
0
Order By: Relevance
“…This result is comparable with the results of studies in AGHD patients with underlying craniopharyngioma [34,35] and with underlying non-functioning pituitary adenoma [36,37], suggesting that Norditropin ® treatment does not increase the risk for the development of these diseases. In fact, a recently published statement asserts that available data do not indicate an increased risk of new primary cancers or recurrence of primary cancer in AGHD patients [38].…”
Section: Discussionsupporting
confidence: 83%
“…This result is comparable with the results of studies in AGHD patients with underlying craniopharyngioma [34,35] and with underlying non-functioning pituitary adenoma [36,37], suggesting that Norditropin ® treatment does not increase the risk for the development of these diseases. In fact, a recently published statement asserts that available data do not indicate an increased risk of new primary cancers or recurrence of primary cancer in AGHD patients [38].…”
Section: Discussionsupporting
confidence: 83%
“…Additional characteristics of the included studies are shown in Table 1. As shown in table, seven of the selected studies obtained seven or more scores, which indicated that the study quality was relatively higher [5][6][7][14][15][16][17][18][19][20][21][22]; whereas, other studies with relatively lesser scores were considered of lower quality [23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [5,19,20,22] assessed the relationship between GHRT and risk of recurrence/progression in pituitary adenomas. The cumulative estimated risk associated with GH use was 0.85 (95 % CI 0.65-1.11; I 2 = 16.6 %, p for heterogeneity = 0.309).…”
Section: Ghrt For Pituitary Adenomasmentioning
confidence: 99%
“…Recent findings indicate that this is not the case in patients with NFPA (17,18). It is well known that CPs have a high tumour progression rate -in fact after 10 years of follow-up around half of all CP patients who have not received RT develop tumour progression (1).…”
Section: Introductionmentioning
confidence: 99%